Influence of inhibitor on corrosion behaviour of Al-Mg alloy / Muhamad Nur Irfan Mohd Adly - Muhamad Nur Irfan, Mohd Adly (2021)
From pure aluminium to a series of aluminium alloy, the evolution of the steel led by a continuous demand for a superior and more efficient steel. Since then, aluminium alloy have been employed in numerous engineering applications such as engine parts, marine applications, and other applications demands the large volumes of aluminium alloys. However, Al-Mg are exposed to continuous attacks from corrosion, thus usage of corrosion inhibitors is necessary to enhance Al-Mg corrosion resistance. The aim of this research is to study the previous literature journal on the effect of inorganic inhibitor on Al-Mg in corrosive media and surface morphology of Al-Mg with or without inorganic inhibitors from. Electrochemical corrosion testing was performed on Al-Mg alloy with various type corrosive media and inorganic inhibitor. The corrosion mechanism with or without inhibited on Al-Mg was observed by potentiodynamic polarization study. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were used to investigate the surface microstructure morphology. The result from the reviewed journal shows that the Al-Mg was seriously corroded under acidic corrosive media due to the aggressive ion. Addition of inorganic inhibitors such as chromates, molybdates, phosphates and nitrates proved to reduce the rate of corrosion of the Al-Mg alloy. The result from the literature also confirmed that higher concentration will give a better corrosion protection. Inorganic inhibitor molecules suppress corrosion by adsorbing to the alloy surface, forming an exterior protective coating that prevents corrosion. The result was confirmed and reviewed by the electrochemical measurements, scanning electron microscopy (SEM) as well as energy dispersive X-ray spectroscopy (EDS).